Synergistic adsorption-photocatalytic degradation of Rhodamine B dye using a 3D-printed photoreactor with g-CN homojunction-based thermosets coating: response surface methodology and adsorption modelling. Issue 1 (1st October 2022) - Lee, EY; Wong, SY; Wong, VL; Phang, SJ; Cheah, KH
Abstract: In present work, graphitic carbon nitride (g-CN) homojunction were synthesized to investigate the synergistic effect of photocatalysis and adsorption on Rhodamine B (RhB) dye degradation. The photodegradation (DE%) and adsorption (R%) were evaluated under the irradiation of two 50 W LED lights and in dark for 6 hours, respectively. A three-level Box-Behnken design (BBD) were employed to study the effects of initial dye concentrations (5 to 20 ppm), recirculation flow rates (1 to 3 mL/min), and the number of photoreactors (2 to 6) with total 15 sets of experiment. A quadratic regression was developed to predict DE% with an error of less than 5.5% relative to the experimental data. Additionally, ANOVA analysis showed that the number of photoreactors is the most influential parameter (p<0.05); while the two-way interaction between variables are insignificant. For the adsorption studies, Langmuir isotherm showed the best-fit result (R 2 >0.98) and the separation factor (RL ) has indicated the adsorption process is favourable (RL =0.05). Additionally, the adsorption experimental data fit well with the pseudo-second-order kinetic model (R 2 >0.98). Overall, the development of homojunction photocatalyst has provided an innovative and alternative approach for water remediation.